Kekuasaan Mahkamah Konstitusi dalam Merekonsiliasi Konflik Politik: Sebuah Tinjauan terhadap Putusan Kontroversial - Syah Ramadhan Putra (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The Constitutional Court (MK) should function as the final fortress of the constitution, yet this research reveals its paradoxical role: instead of mitigating political conflict, several of its controversial rulings have become catalysts for a legitimacy crisis and profound polarization. Through a critical study of pivotal decisions (including the Presidential/Vice Presidential Age Limit ruling, the KPK Law review, and the 2024 Presidential Election Dispute), this normative legal analysis highlights the failure of substantive reconciliation in Indonesia. The MK Ruling No. 90/PUU-XXI/2023, shrouded in conflict of interest and ethical sanctions, demonstrates the Court's vulnerability to constitutional manipulation. Similarly, the KPK Law ruling effectively legitimized the weakening of the anti-corruption body, and the 2024 Election Dispute was marked by judicial division (dissenting opinions). The implications are staggering: the emergence of tension between formal legal certainty and moral justice. The MK now stands at a crossroads, will it restore its integrity as a true guardian of the constitution or merely serve as a tool for legitimizing power?.